The relationship between relative age effects and sex, age categories and playing positions in Brazilian National Handball Teams - Lucas Savassi Figueiredo; Petrus Gantois; Dalton de Lima-Junior; Leonardo de Sousa Fortes; Fabiano de Souza Fonseca (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: This study investigated the existence of Relative Age Effect (RAE) in the selection process of male and female athletes in the Brazilian national handball teams according to age categories (U-18, U-21, and senior) and playing position (wings, backs, pivots, and goalkeepers). Methods: In order to determine RAE, athletes were divided based on their months of birth; quarters Q1 (January-March), Q2 (April-June), Q3 (July-September), and Q4 (October-December). Data were collected from the official Brazilian Handball Confederation (CBHb) website and included the athletes that participated in training and/or competitions composing the Brazilian national teams from 2014 to 2018. To determine the RAE on playing positions, age categories of male and female groups were pooled. Chi-squared tests were performed to investigate the RAE. Results: An over-representation of players born in Q1 and Q2 in the U-18, U-20, and senior categories of male teams and the U-20, and senior female teams were found. In the male teams, as the age category increased, RAE decreased, but still existed. Such distribution was reversed in the female athletes, with a higher RAE magnitude in the senior category as compared to U-18 and U-21. Additionally, it seems that RAE is dependent on the playing position only for male athletes (wings and backs) whereas RAE was found for all playing positions in female athletes. Conclusion: Overall, RAE was found in Brazilian national handball teams, but its magnitude and form of manifestation seem to be influenced by sex, category, and playing position.